2019
DOI: 10.2903/j.efsa.2019.5848
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetically modified maize MON 87427 × MON 89034 × MIR162 × MON 87411 and subcombinations, for food and feed uses, under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐NL‐2017‐144)

Abstract: Maize MON 87427 × MON 89034 × MIR162 × MON 87411 (four‐event stack maize) was produced by conventional crossing to combine four single events: MON 87427, MON 89034, MIR162 and MON 87411. The genetically modified organism (GMO) Panel previously assessed the four single maize events and four of the subcombinations and did not identify safety concerns. No new data on the single maize events or the four subcombinations that could lead to modification of the original conclusions on their safety were identified. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
7
3
0
Order By: Relevance
“…In addition, the updated bioinformatic analysis of the newly created ORFs spanning the junctions with genomic DNA confirms previous results which did not indicate sequence similarities to toxins or allergens in maize MIR162 (EFSA, 2012;EFSA GMO Panel, 2019. The updated bioinformatic analyses for event MIR162 did not reveal any DNA sequence that could provide sufficient length and identity which could facilitate horizontal gene transfer (HGT) by double homologous recombination, confirming previous conclusions (EFSA, 2012;EFSA GMO Panel, 2019. Given the results of this analysis and that the recombinant DNA in maize MIR162 does not confer selective advantages to microorganisms, the GMO Panel identified no safety concern linked to an unlikely but theoretically possible HGT.…”
Section: Evaluation Of the Updated Bioinformatic Datasupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, the updated bioinformatic analysis of the newly created ORFs spanning the junctions with genomic DNA confirms previous results which did not indicate sequence similarities to toxins or allergens in maize MIR162 (EFSA, 2012;EFSA GMO Panel, 2019. The updated bioinformatic analyses for event MIR162 did not reveal any DNA sequence that could provide sufficient length and identity which could facilitate horizontal gene transfer (HGT) by double homologous recombination, confirming previous conclusions (EFSA, 2012;EFSA GMO Panel, 2019. Given the results of this analysis and that the recombinant DNA in maize MIR162 does not confer selective advantages to microorganisms, the GMO Panel identified no safety concern linked to an unlikely but theoretically possible HGT.…”
Section: Evaluation Of the Updated Bioinformatic Datasupporting
confidence: 86%
“…The updated bioinformatic analyses for event MIR162 did not reveal any DNA sequence that could provide sufficient length and identity which could facilitate horizontal gene transfer (HGT) by double homologous recombination, confirming previous conclusions (EFSA, 2012; EFSA GMO Panel, 2019, 2021). Given the results of this analysis and that the recombinant DNA in maize MIR162 does not confer selective advantages to microorganisms, the GMO Panel identified no safety concern linked to an unlikely but theoretically possible HGT.…”
Section: Assessmentsupporting
confidence: 77%
“…MON-87411 has been registered for cultivation in the US and elsewhere since 2015 ( Firko, 2015 ). The grain product of this crop has been registered for food and feed uses within the European Union ( Naegeli et al, 2019 ). To date, no other dsRNA-based GM crop has been commercialized.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018–2021, EFSA evaluated the safety of MON87411 with other GM corns for food and feed uses. EFSA concluded that MON87411 was safe, and no safety concern was identified ( EFSA Panel on Genetically Modified Organisms (GMO) et al, 2018 , 2019 , 2021 ). In 2021, the GMO safety certificate of MON87411 was approved by Ministry of Agriculture and Rural Affairs, PRC.…”
Section: The Safety Assessment Of Rnai-based Pest Control Strategiesmentioning
confidence: 99%